2022
DOI: 10.1051/nso/2021001
|View full text |Cite
|
Sign up to set email alerts
|

South-hemispheric marine aerosol Hg and S isotope compositions reveal different oxidation pathways

Abstract: Particle-bound mercury (PBM) records the oxidation of elemental mercury, of which the main oxidation pathways (Brž/Clž/OHž/O3) remain unclear, especially in the Southern-Hemisphere. Here, we present latitudinal covariations of Hg and S-isotopic anomalies in cross-hemispheric marine aerosols that evidence an equator-to-poleward transition of Hg oxidants from OHž/O3 in tropics to Brž/Clž in polar regions highlighting thus the presence of distinct oxidation processes producing PBM. The correlations between Hg, S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…The three scenarios (Run1–3) simulate drastically different odd-MIF of Hg II (P) [Δ 199 Hg II (P) and Δ 201 Hg II (P)] in the global atmosphere (Figure S1), even though all reproduce the global spatial variability of observed TGM and wet deposition (see Supporting Information Appendix, Text S1). We synthesized globe observations of Δ 199 Hg II (P) and Δ 201 Hg II (P) that contain sites in land and MBL (Figure A). ,, , , , We find that Run1 simulates Δ 199 Hg II (P) and Δ 201 Hg II (P) values (0.04 ± 0.29‰ and 0.05 ± 0.29‰, respectively) comparable to observations (0.08 ± 0.29‰ and 0.06 ± 0.27‰, respectively). Moreover, only Run1 produces comparable Δ 199 Hg II (P) and Δ 201 Hg II (P) values across the three categorized observations (Table S2).…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…The three scenarios (Run1–3) simulate drastically different odd-MIF of Hg II (P) [Δ 199 Hg II (P) and Δ 201 Hg II (P)] in the global atmosphere (Figure S1), even though all reproduce the global spatial variability of observed TGM and wet deposition (see Supporting Information Appendix, Text S1). We synthesized globe observations of Δ 199 Hg II (P) and Δ 201 Hg II (P) that contain sites in land and MBL (Figure A). ,, , , , We find that Run1 simulates Δ 199 Hg II (P) and Δ 201 Hg II (P) values (0.04 ± 0.29‰ and 0.05 ± 0.29‰, respectively) comparable to observations (0.08 ± 0.29‰ and 0.06 ± 0.27‰, respectively). Moreover, only Run1 produces comparable Δ 199 Hg II (P) and Δ 201 Hg II (P) values across the three categorized observations (Table S2).…”
Section: Resultsmentioning
confidence: 58%
“…However, recent isotope data have raised uncertainties regarding the Hg 0 oxidation pathway in the MBL. For instance, based on cross-hemispheric sulfur and Hg isotope data on marine aerosols, AuYang et al proposed that Hg oxidation is primarily driven by OH/O 3 in the tropics, transitioning to Br/Cl in polar regions. On the other hand, Yu et al and Qiu et al found that Hg 0 oxidation in North Hemisphere tropical and temperate MBL is mainly initiated by Br through Hg isotope analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations